Development of the NASA-TLX Multi Equation Tool to Assess Workload - Campoya Morales, Ángel Fabián; Maldonado-Macías, Aide Aracely; Hernandez Arellano, Juan Luis; Gonález Muñoz, Elvia Luz (2020)
The NASA-TLX method has been used more than 20 years to assess mental workload. NASA-TLX is a multidimensional technique to provide a score based on six subscales: mental demand, physical demand, temporal demand, performance, effort, and frustration level. Although some researchers have developed software to facilitate the application of the method, all the versions created use a single form of evaluation. Throughout a literature review, four different equations to apply NASA-TLX where identified. The objective of this investigation is to develop the NASA-TLX Multi Equation Tool (MET) programmed with the four different equations. The software was created in HTML format with JavaScript. As a result, the software shows the workload assessment with the four different equations.